Monetary policy in the liquidity trap and after: A reassessment of quantitative easing and critique of the Federal Reserve's proposed exit strategy - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper provides a novel analysis of quantitative easing (QE) that focuses on its implicit fiscal dimension. The first segment examines the theory of the liquidity trap and introduces a distinction between a "weak" and "strong" liquidity trap. The second segment analyzes the impact of QE under conditions of a weak and strong liquidity trap. In a weak liquidity trap QE is expansionary but subject to diminishing returns. As QE involves purchasing assets from the public, it transfers the income streams associated with those assets to the fiscal authority. This transfer generates a form of fiscal drag that can theoretically eventually render QE contractionary. In an open economy, exchange rate effects of QE also need to be taken account of and those tend to be expansionary. The third segment explores how to exit QE. The current suggestion of raising the policy interest rate and paying interest on reserves to check inflationary pressures is contradicted because paying interest constitutes an implicit tax cut. Instead, the paper suggests adopting a system of asset based reserve requirements. Requiring banks to hold increased reserves would permanently deactivate liquidity created by QE without recourse to interest payments and the implicit tax cut they represent.
urn:nbn:de:101:1-201403118386
Keywords: E43; E44; E50; E52; E58; 330; quantitative easing; fiscal drag; interest on reserves; exit strategy; asset based reserve requirements; Geldpolitik; Steuerprogression; Mindestreserve; Deutschland